2015
DOI: 10.1016/j.fm.2015.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Microbial biogeography of the transnational fermented milk matsoni

Abstract: The fermented milk matsoni is a traditional, national food product of both Georgia and Armenia. Little is known about the effects of biogeography and milk type on the microbial biodiversity of matsoni or the fungal composition of matsoni fermentations. High-throughput marker-gene sequencing was used to survey the bacterial and fungal communities of matsoni from different milk types and regions throughout Armenia and Georgia. Results demonstrate that both production region and milk type influence matsoni microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 30 publications
3
41
1
2
Order By: Relevance
“…faecium in Georgian yoghurt samples was isolated L. acidophillus, L. casei, S. termophilus, L. lactis, L. diacetylactis, Ent. durans but have not met the bacteria L. bulgaricus [4].Our findings show that isolated LAB from samples of matsun of Nagorno Karabakh contain LAB Ent. faecium, Ent.durans, which exhibit probiotic properties and the ability to inhibit the growth of some antibiotic-resistants strains.…”
Section: Investigation Of the Properties Of Endemic Lab Strains Of Gementioning
confidence: 63%
“…faecium in Georgian yoghurt samples was isolated L. acidophillus, L. casei, S. termophilus, L. lactis, L. diacetylactis, Ent. durans but have not met the bacteria L. bulgaricus [4].Our findings show that isolated LAB from samples of matsun of Nagorno Karabakh contain LAB Ent. faecium, Ent.durans, which exhibit probiotic properties and the ability to inhibit the growth of some antibiotic-resistants strains.…”
Section: Investigation Of the Properties Of Endemic Lab Strains Of Gementioning
confidence: 63%
“…Products such as matsoni, a fermented milk product of Armenian origin, and kule naoto, the traditional fermented milk product of the Maasai in Kenya, are having their previously undescribed microbiotas characterised using sequencing-based analysis 37, 38 . Indeed, such products may be of great value: for example shubat, a probiotic fermented camel milk of Kazakh origin, has recently been found to demonstrate positive hypoglycaemic activity in type 2 diabetic rats 39 , and the indigenous Indian fermented beverage Raabadi has been investigated as a source of probiotic hypocholesterolaemic lactobacilli 40 .…”
Section: Ethnic Fermented Milk Productsmentioning
confidence: 99%
“…Thus, high-throughput sequencing technologies are providing the greatest advance to this sector of research, where the increased sample throughput and detection sensitivity support analysis of larger and more complex studies. Amplicon sequencing approaches have been applied to study the microbial ecology of pearl millet fermentations [6], various Asian vegetable fermentations [79], seafood fermentations [10], Chinese liquor [11], cheese [1214], sake [15] and other rice beers [16], olives [17], sourdough [18], kombucha [19], kefir and similar fermentations [20,21], wine [22,23], and spontaneously fermented American coolship ale fermentations [24,25]. What types of questions can be answered from describing the microbial succession in these fermented foods?…”
Section: Application Of Microbial System-level Tools In Food Productionmentioning
confidence: 99%
“…Bokulich et al . [21] demonstrated that both production region and milk type influence the microbiota content of fermented matsoni (a fermented milk in the Caucasus region), suggesting that the traditional production methods preserve the transfer of unique regional microbiota from batch to batch. However, other aspects of dairy products do not show similar regionality.…”
Section: A New Concept Of ‘Microbial Terroir’mentioning
confidence: 99%